Experimental study on web crippling of high strength steel channel sections under end two flange loading condition - Kaung, Si Thu (Nanyang Technological University, 2021)
This report presents an experimental study on web crippling of high strength steel S690 and S960 channels. Six S690 steel specimens and four S960 steel channel section specimens were tested under end two flange (ETF) loading condition. The corresponding test set-up, experimental procedures, load-deformation curves, and ultimate loads were reported in detail. Given that design rules for high strength steel channels under ETF loading are not available, the obtained test results were compared with resistance predictions from (i) Eurocode EN 1993-1-3, (ii) American specification AISI S100 to assess the suitability of the codified design equations for the high strength steel channels. The comparison study shows that the EN 1993-1-3 provides conservative resistance predictions whereas the AISI S100 gives overly unconservative capacity estimations.